On the complexities of utilizing large‐scale lightpath‐connected distributed cyberinfrastructure. (19th May 2016) - Maassen, Jason; van Werkhoven, Ben; van Meersbergen, Maarten; Bal, Henri E.; Kliphuis, Michael; Brunnabend, Sandra E.; Dijkstra, Henk A.; van Malenstein, Gerben; de Vos, Migiel; Kuijpers, Sylvia; Boele, Sander; Wolfrat, Jules; et al.
Summary: In Autumn 2013, we—an international team of climate scientists, computer scientists, eScience researchers, and e‐Infrastructure specialists—participated in the enlighten your research global competition, organized to showcase advanced lightpath technologies in support of state‐of‐the‐art research questions. As one of the winning entries, our enlighten your research global team embarked on a very ambitious project to run an extremely high resolution climate model on a collection of supercomputers distributed over two continents and connected using an advanced 10 G lightpath networking infrastructure. Although good progress was made, we were not able to perform all desired experiments due to a varying combination of technical problems, configuration issues, policy limitations and lack of (budget for) human resources to solve these issues. In this paper, we describe our goals, the technical and non‐technical barriers, we encountered and provide recommendations on how these barriers can be removed so future project of this kind may succeed. Copyright © 2016 John Wiley & Sons, Ltd.